Peroxy ethoxyformyl nitrate, CH3CH2OC(O)OONO2. Spectroscopic and thermal characterization - Bossolasco, Adriana Gabriela (2011)
Synthesis of CH3CH2OC(O)OONO2 was carried out from the photolysis of a mixture of ethyl formate (CH3CH2OC(O)H), Cl2, NO2, and O2 at 253K using UV radiation. It was characterized by IR, UV spectroscopy,and mass spectrometry. Thermal decomposition was studied between 279 and 301 K, at totalpressures of 1 atm. The pressure dependence of the reaction rate constant was studied at 298K from 7 to 1000 mbar. The activation energy was determined at a total pressure of 1 atm, ensuring that kinetic studies were performed in the high pressure limit. The DFT method [B3LYP/6.31++G(d,p)] was used to identify the most stable rotamer as well as its geometric parameters and energetics.At room temperature, CH3CH2OC(O)OONO2 is stable for several days in the gas state, as revealed by its measured lifetime. The atmospheric implications of this finding are discussed.